2004
DOI: 10.5194/acpd-4-6127-2004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The North Atlantic variability structure, storm tracks, and precipitation depending on the polar vortex strength

Abstract: Abstract. There is ample evidence that the state of the northern polar stratospheric vortex in boreal winter influences tropospheric variability. Therefore, the main teleconnection patterns over the North Atlantic are defined separately for winter episodes in which the zonal mean wind at 50 hPa and 65° N is above or below the critical Rossby velocity for zonal planetary wave one. It turns out that the teleconnection structure in the middle and upper troposphere differs considerably between the two regimes of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…Many recent studies showed that the stratospheric polar vortex is implicated in a variety of atmospheric processes including the formation of ozone holes in the Antarctic, the North-Atlantic Oscillation (NAO) and the Arctic Oscillation (AO), interannual and secular climate variability (e.g., Solomon, 1990;Tompson and Wallace, 1998;Baldwin and Dunkerton, 2001;Walter and Graf, 2005;Frolov et al, 2009;Gudkovich et al, 2009, etc.). In particular, the temperature drop below À80°C inside the vortex produces favorable conditions for the formation of polar stratospheric clouds (PSC).…”
Section: Stratospheric Vortex As An Important Factor Of the Largescalmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies showed that the stratospheric polar vortex is implicated in a variety of atmospheric processes including the formation of ozone holes in the Antarctic, the North-Atlantic Oscillation (NAO) and the Arctic Oscillation (AO), interannual and secular climate variability (e.g., Solomon, 1990;Tompson and Wallace, 1998;Baldwin and Dunkerton, 2001;Walter and Graf, 2005;Frolov et al, 2009;Gudkovich et al, 2009, etc.). In particular, the temperature drop below À80°C inside the vortex produces favorable conditions for the formation of polar stratospheric clouds (PSC).…”
Section: Stratospheric Vortex As An Important Factor Of the Largescalmentioning
confidence: 99%
“…According to Baldwin and Dunkerton (2001), more positive values of the NAO and AO indices are associated with strong vortex conditions. In turn, the changes of the NAO under strong and weak vortex regimes influence the average latitude of cyclone tracks, which are shifted to the north when the NAO is positive, and, respectively, temperature and precipitation over Europe (Baldwin and Dunkerton, 2001;Walter and Graf, 2005). The data presented by Frolov et al (2009) andGudkovich et al (2009) show that the rotation of cold and warm epochs in the Arctic region is related to the changes of the polar vortex state, warm and cold periods being associated with a strong and weak vortex, respectively.…”
Section: Stratospheric Vortex As An Important Factor Of the Largescalmentioning
confidence: 99%
“…The strength of the polar vortex has been discussed as a forcing mechanism on the climate variability over the North Atlantic region and also as a mechanism to explain large-scale teleconnection patterns Walter and Graf, 2005). The polar vortex is a persistent large-scale cyclonic circulation pattern in the middle and upper troposphere and the stratosphere, centred generally in the polar regions of each hemisphere.…”
Section: Winter Precipitation Anomalies Along the Western Coast Of Nomentioning
confidence: 99%
“…During the latest years, however, it is shown that one of the two polarities of the leading mode of the North Atlantic storm-track variability corresponds to a blocking situation of the NE Atlantic with a strong north-eastward tilt of the storm-track axis and reduced precipitation in western Europe. This situation is, however not captured by standard NAO indices (Rogers, 1997;Shabbar et al, 2001), and reanalyses using data of geopotential height, air temperature, wind and precipitation for the high-latitude Northern Hemisphere suggests that it is necessary to include the state of the polar vortex in any study of North Atlantic climate variability Walter and Graf, 2005). Walter and Graf (2005) suggest that precipitation anomalies at the west coast of Greenland and the anomalies at the Norwegian coast could serve as a proxy for the strength of the polar vortex.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation